2024
DOI: 10.1124/jpet.123.001817
|View full text |Cite
|
Sign up to set email alerts
|

Protective Activity of Novel Hydrophilic Synthetic Neurosteroids on Organophosphate Status Epilepticus-induced Chronic Epileptic Seizures, Non-Convulsive Discharges, High-Frequency Oscillations, and Electrographic Ictal Biomarkers

Sreevidhya Ramakrishnan,
Tanveer Singh,
Doodipala Samba Reddy

Abstract: Nerve agents and organophosphates (OP) are neurotoxic chemicals that induce acute seizures, status epilepticus (SE), and mortality. Long-term neurologic and neurodegenerative effects manifest months to years after OP exposure. Current benzodiazepine anticonvulsants are ineffective in preventing such long-term neurobehavioral and neuropathological changes. New and effective anticonvulsants are needed for OP intoxication, especially for mitigating the long-term sequelae after acute exposure. We developed neurost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…The observed improvements in neuropathological defects align with the improvement of neurologic functional deficits. As projected, VX and LX elicited protection against OP-induced SE, chronic epileptic seizures, and ictal biomarkers in the DFP model ( Ramakrishnan et al, 2024 ). Together, these findings establish VX and LX as potent and efficacious synthetic neurosteroids with drug-like properties suitable for counteracting the long-term neuropsychiatric sequel following OP exposure.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The observed improvements in neuropathological defects align with the improvement of neurologic functional deficits. As projected, VX and LX elicited protection against OP-induced SE, chronic epileptic seizures, and ictal biomarkers in the DFP model ( Ramakrishnan et al, 2024 ). Together, these findings establish VX and LX as potent and efficacious synthetic neurosteroids with drug-like properties suitable for counteracting the long-term neuropsychiatric sequel following OP exposure.…”
Section: Discussionmentioning
confidence: 93%
“…Neurosteroid analogs decreased degeneration of neurons, specifically inhibitory interneurons in the hippocampus and other regions. Moreover, they exhibit striking disease-modifying effects on DFP-induced long-term epileptic seizures and discharges ( Ramakrishnan et al, 2024 ). These mechanistic and neuropathological improvements likely led to the protective effects observed in seizure outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When tested in animal models of OPNA-induced RSE, these lead analogs effectively blocked RSE when given intramuscularly 40 minutes after DFP administration, indicating their efficacy in the DFP model. The lead analogs significantly reduced neuronal injury, neurodegeneration, and inflammation in the hippocampus and other regions ( Ramakrishnan et al, 2024 ; Reddy et al, 2024 ), suggesting their neuroprotectant potential to mitigate OPNA-induced brain damage. The most promising drug-like compounds are in advanced development as anticonvulsants and neuroprotectants for SE indications.…”
Section: Novel Synthetic Neurosteroids (Superganaxolones) For Rsementioning
confidence: 92%
“…Reddy and team have developed novel hydrophilic neurosteroids, such as valaxanolone and lysaxanolone, showing promising results in animal studies. In an antiseizure study, Reddy’s team reported valaxanolone and lysaxanolone effectively protected against DFP-induced epileptic seizures and electrographic biomarkers of ictal activity ( Ramakrishnan et al, 2024 ). In a neuroprotection study, Reddy and the team found that valaxanolone and lysaxanolone significantly improved behavioral and memory deficits, correlated with their ability to reduce neurodegeneration and neuroinflammation ( Reddy et al, 2024 ).…”
Section: Nerve Agentsmentioning
confidence: 99%